TRANSFORMASI AL-QUR’AN DARI TRADISI LISAN KE KODIFIKASI MUSHAF: Kajian Filologis dan Historis - Ramlah; Nasrullah Bin Sapa; Halimah Basri (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2025)
This article aims to examine the transformation of the Qur’an from oral tradition to written manuscript as a pivotal event in the history of Islamic civilization. This process involved rigorous methodological steps and visionary strategic decisions, particularly during the caliphates of Abu Bakr and Uthman ibn Affan. Using a qualitative approach based on library research, this study explores the methods of compilation, verification, and standardization of the Qur’anic manuscripts, as well as their impact on the development of Islamic sciences and the unity of the Muslim community. The codification of the Qur’an not only preserved the authenticity of divine revelation across generations but also facilitated the spread of Islamic civilization to diverse regions worldwide. In the modern context, the digitalization of the Qur’an enhances accessibility but presents new challenges, such as ensuring the authenticity of texts in the digital era. This study provides a profound understanding of the relevance of Qur’anic codification as a foundation for Islamic scholarship and identity.